Penggunaan Model Pembelajaran Collaborative Learning (CBL) Dalam Proses Pembelajaran IPS di SD - Anis Yuliani; Novia Sagita Haryati; Upy Syarifah (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
The learning model is something that needs to be considered in social studies learning in elementary schools in order to improve student learning activities by using the Collaborative Learning (CbL) learning model. This study aims to identify the use of Collaborative Learning (CbL) learning models in social studies learning in elementary schools. This research uses literature or literature study methods. Where data collection is taken from various journals, articles and books. The research results obtained are Collaborative Learning (CbL) learning models are suitable for use in social studies learning in elementary schools because the Collaborative Learning (CbL) learning model can make students more receptive to social studies learning so that it can increase student activity, cooperation, mutual attitude. respect and social attitudes. Thus, it can be used as a support or encouragement in carrying out the social studies learning process in elementary schools so that students can increase knowledge of the communication that occurs between students so that the learning process becomes more communicative and the social level between students also increases.